The Effect of Various Learning Aids in the Development of Some of the Basic Skills of Basketball for the Intermediate Second-Grade Students - Salman, Janan; Abdul Kadim, Raad (Journal of Physical Education, 2015)
The first part of this thesis consists of an introduction and the importance of this research as the researcher touched to the teaching aids. These aids play a broad role in the process of cognition because of it's all potential used by the teachers that are working on. These tools clarify and transports information to the learner in order to reach their goal. The teacher usually uses appropriate learning aids for students to help the delivery of information to learners; regardless of differences that can be included that appeared in receiving information. Therefore, different educational tools must be used to reduce these differences and learning in the shortest time, and with less effort, and especially during the teaching of basketball game which is a group games that are taught at the intermediate level within the Ministry of Education curriculum. The game consists of skills requires interaction between the teacher and the learner. So the research problem has been selected through the use of different teaching aids to reduce these differences and learning the shortest time, and with less effort. As for the second part of this thesis, the researcher has touched the concept of educational methods and their role in the development of some basic skills in basketball. In part three the researcher has handled the methodology used, the sample of research, the research tools and the tests of basketball skills. In this work, the experimental method has been used on group samples composed of three groups (aural-visual-sensual). Part four includes the presentation of the results, discussion and analysis of this study. Finally, as for part five the researcher has concluded the following: The impact of using teaching aids in the curriculum was effective to improve and develop the skill side of the three experimental groups (aural-visual-sensual) for the reason of its diversity. Recommendations: 1. The physical education teachers should have the necessity of knowing the needs to define the use of teaching aids in physical education lesson, and their impact on the development of movement skills of the present reasearch and opening courses on how to use them. 2. Conducting similar studies on different samples, and different sports and events